Lidar measurements of aerosol and ozone distributions during the 1992 Airborne Arctic Stratospheric Expedition - Browell, E. V.; Butler, C. F.; Fenn, M. A.; Grant, W. B.; Carter, A. F. (1992)
The LaRC airborne lidar system was operated from the ARC DC-8 aircraft during the 1992 Airborne Arctic Stratospheric Expedition (ASEE-2) to investigate the distribution of stratospheric aerosols and O3 across the Arctic vortex from Jan. to Mar. 1992. Monthly flights were made across the Arctic vortex from Anchorage, Alaska, to Stavanger, Norway, and then back to Bangor, Maine, and additional round-trip flights north into the vortex were made each month from either Stavanger or Bangor depending on the location of the vortex that month. The airborne lidar system uses the differential absorption lidar (DIAL) technique at laser wavelengths of 301.5 and 310.8 nm to measure O3 profiles above the DC-8 over the 12-25 km altitude range. Lidar measurements of aerosol backscatter and depolarization profiles over the 12-30 km altitude range are made simultaneously with the O3 measurements using infrared (IR) and visible (VIS) laser wavelengths of 603 and 1064 nm, respectively. The measurements of Pinatubo aerosols, polar stratospheric clouds, and O3 made with the airborne DIAL system during the AASE-2 expedition and to chemical and dynamical process that contribute to O3 depletion in the wintertime Arctic stratosphere.